Sistem Kontrol dan Monitoring Penggunaan Air Berbasis IoT Menggunakan Modul ESP8266 - Nur Imansyah; Sri Handani Widiastuti (SEULANGA SYSTEM PUBLISHER, 2022)
Water is needed by households or businesses. The amount of water used has an impact on the costs incurred. These costs are getting out of control if the use is not controlled. Users only know after the payment period is due. This cost can be controlled if the amount of water used can be controlled. Even though the water supply company already has a system with a usage meter, users still find it difficult to read the device and the amount of usage costs at that time. So this research was carried out with the aim of building a water use control system for Internet of Things (IoT) based water supply service customers. This system is connected to the user's mobile device via an internet connection so that it can control water use in real time. This system uses the ESP826 microcontroller device. The results of this study can monitor and control in real time the use of water properly. So that this system becomes a reference in reducing the cost of water usage which is controlled in real time